Implementasi Sensor Inertial Measurement Unit (IMU) untuk Monitoring Perilaku Roket - Mudarris Mudarris; Satria Gunawan Zain (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2020)
This paper examines the Implementation of the Inertial Measurement Unit (IMU) Sensor for Monitoring Rocket Attitude. The monitored rocket attitude data is in the form of vibration which is generated by the payload during the functional test and flight speed, acceleration and direction flight test. The rocket payload device is mounted in the rocket compartment for the function of measuring rocket behavior. Data is sent to ground stations via telemetry devices use baud rate of 57600. Based on the results of G-Shock, G-Force and Vibration testing shows that the payload can work well. In accordance with the results of reading the data on the Graphical user Interface (GUI) can be displayed and shows the rocket payload works well. This rocket payload can transmit data remotely.